Effect of use varying ratios from fat with minced meat on bacterial load - salum, Fouad kamil (The Iraqi Journal of Veterinary Medicine, 2010)
This study designed to know the effect of use different ration from mixing between minced meat With fat on total bacterial count of meat ( 80) sample was examine through the period of this study (40 sample for minced meat and 40 sample for minced fat) collected from shops in Baghdad city. The results showed the means of bacterial count was rise for the group contained just minced meat without any mixing in means reach to 9.6x 10 cfu \ml follow it with second group which include only minced fat by count 5.5x10 cfu\ml, and the study showed also decrease in bacterial count for (3) mixing groups ( fat with meat ), so the bacteria count for the third group which included 5%, from fat 1.1x10 cfu\ml and 1.3x10 for each of fourth and fifth group which contain the percent of fat10%,20%0n respectively. Also the study shows presence of a significant difference in ( p<0.05) between different mixing group (meat with fat) from one side to two qroups which included meat and fat only. Also recorded significant difference and in the same level in the mean of bacterial count between the first group which contain minced meat only, and the second one which contain fat only, there is no significant difference in mean of bacterial count among varying mixing group from statistical side but record obvious and important decline hygienically in bacterial count for each group. The study showed the best mixing percent for fat with minced meat were 10%,20% respectively which recorded the less bacterial count in each of these two groups. Conclusion mix fat with meat in ratios (10% - 20%) to get the beast decreas in bacterial load of meat .